Extrativismo do butiá e do pinhão na região dos Campos de Cima da Serra (RS): a valorização da sociobiodiversidade por assentados e comunidades tradicionais - Bellé, Adilson Roberto (2014)
This study aims to understand the conceptions about the process of appropriation of butia (Butia eriospatha) and pinion, seed of Araucaria (Araucaria angustifolia), present in Araucaria Forest - in the region of the Campos de Cima da Serra of Rio Grande do Sul (RS), Brazil - through the process of extraction adopted by settlers for land reform and traditional extractive community. The subjects of this study were a group of six settled families living in Nova Esmeralda Settlement, located in the city of Pinhal da Serra (RS), which comes from the year 2010 involving the extraction of butia to other productive activities of its production plant families and a group of eleven families of extractive pinion in the city of Muitos Capões (RS), which historically developed this activity. The method employed was qualitative research that seeks to understand the social, cultural, economic and ecological conditions studied by the studied subjects and from the concepts that explain the uses and purposes of these native species. The research included a literature and document review; interviews to both groups as well to key informants and technical advisory organizations. For data analysis, we attempted to reference in Oliveira (2012), which points as a method of defining units of analysis as well as theoretical and empirical categories. The literature review focused on the process of social metabolism and metabolism with nature, which focused on the appropriation process of nature. Besides, there were sought references about the ecological culture and environmental rationality to understand the processes that occur in traditional communities and with peasants. And also biodiversity conservation stimulated by its use. The study is completed by pointing out that the economic dimension is the aspect of larger motivation in the two largest public studied, whatever the use in feeding is resident, the common understanding between the two audiences is conservation of Araucaria and butia to continue generating income. The cultural dimension was also present especially in extractive pinion people, who have a long-standing traditional knowledge. The dimension of social organization is more evident in settlers. The extent of conservation is increasingly evident when the nature's resources generate greater economic value. Finally, it is mentioned that nowadays there is a sustainable metabolism with nature, so that, production systems are redesigned based on Agroecology and incorporate sociobiodiversity species.